Surface relief deformation and microstructure changes during luders band propagation in ARMCO iron at elevated and room temperatures - Danilova, L. V. (AIP Conference Proceedings)
This research has studied the features of the surface relief and the change in the microstructure of ARMCO iron after propagation the deformation front at room and elevated temperatures. The fronts of the Chernov-Luders bands move monotonously at room temperature. This corresponds to the typical stress-strain curve of low-carbon steel. After deformation, shear bands are observed in the material, both in individual grains and conglomerates of grains. At elevated temperatures, the fronts of the Chernov-Luders bands move discretely with stops. In this setting, a serrated deformation is observed on the stress-strain curve. A periodic relief with a spatial period of ~ 6 mm is observed after passage the deformation front at the mesoscopic level.